O ensino de história e o patrimônio em disputa: as casas modernistas de Ponta Grossa/PR - Martins, Lucas Santiago (Universidade Estadual de Ponta Grossa, 2026)
This research addresses the teaching of History through the analysis of three modernist houses located in the central area of Ponta Grossa. This study chose to analyze these buildings through Heritage Education in dialogue with Local History. To this end, the research aimed to analyze three modernist houses in the city, built in the 1940s, 1950s, and 1960s. In addition, this study sought to present and understand how these buildings have undergone heritage listing processes in the present time. The work was grounded in Françoise Choay (1992, 2014) and François Hartog (2003, 2006), providing a theoretical basis on heritage and its variations, such as built heritage. It sought and established theoretical references on modernism and modernist architecture based on the principles of Le Corbusier (1993) and Benevolo (1998), combined with the urban context of the city. It presented architectural and historical characteristics of the constructions. It historically contextualized heritage preservation through institutions at the federal, state, and municipal levels. It discussed and problematized the tensions related to the heritage listing processes of these residences through architectural projects, images, and the minutes of COMPAC (Municipal Council of Cultural Heritage). It sought to address the urban expansion of Ponta Grossa and its increasing verticalization. As a result, a pedagogical proposal for teaching practice aimed at the final years of Elementary School and High School was formalized. Thus, educational material in the form of a catalog was created, with images and texts that sought to promote critical reflection on the processes of heritage valuation and preservation.
Keywords: arquitetura modernista; ensino de história; educação patrimonial; modernist architecture; history teaching; heritage education